1993
DOI: 10.1007/bf00199618
|View full text |Cite
|
Sign up to set email alerts
|

The effect of industrial pollution on copper, lead, zinc and cadmium concentration in xylem rings of resistant (Populus marilandica) and sensitive (P. balsamifera) species of poplar

Abstract: Summary.The patterns of radial distribution of copper, lead, zinc and cadmium in two species of poplar, growing under polluted conditions near a copper smelter, were investigated. Populus marilandica is very resistant to such pollution, but P. balsamifera is sensitive. Soils were examined for concentrations of these metals, and only a surface layer of soil was polluted with copper and lead. P. balsamifera absorbed much more cadmium than P. marilandica under the same conditions. P. marilandica shows a pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…However, the variation is generally higher in the outer, functional part of secondary xylem (sapwood) than in the inner, non-functional part (heartwood). This attests to transport of metals in younger xylem and confirms earlier observations on other tree species (Hagemeyer and Breckle, 1986;Balk and Hagemeyer, 1994;Brackhage et al, 1996;Trüby, 1995;Lukaszewski et al, 1988Lukaszewski et al, , 1993Nabais et al, 1999).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However, the variation is generally higher in the outer, functional part of secondary xylem (sapwood) than in the inner, non-functional part (heartwood). This attests to transport of metals in younger xylem and confirms earlier observations on other tree species (Hagemeyer and Breckle, 1986;Balk and Hagemeyer, 1994;Brackhage et al, 1996;Trüby, 1995;Lukaszewski et al, 1988Lukaszewski et al, , 1993Nabais et al, 1999).…”
Section: Resultssupporting
confidence: 86%
“…Many reports attest to the possible correlation between industrialization and motorization, associated with air pollution, and the level of heavy metals in corresponding growth rings (Ault et al, 1970;Ward et al, 1974;Rolfe, 1974;Kardell and Larsson, 1978;Queirolo et al, 1990). Other authors point to the possibility of radial movement of metals towards heartwood, which contradicts a strong relationship between concentration of heavy metals in successive growth rings and environmental pollution at that time (Hagemeyer and Breckle, 1986;Hagemeyer, 1995;Hagemeyer and Shin, 1995;Balk and Hagemeyer, 1994;Brackhage et al, 1996;Lukaszewski et al, 1988Lukaszewski et al, , 1993Nabais et al, 1999;). It was found that xylem has ion-exchanging properties, as Ca 2+ ions exclude Pb 2+ and Cu 2+ ions from xylem.…”
Section: Introductionmentioning
confidence: 91%
“…Such distribution patterns were transformed into pollution chronologies. The results of these dendroanalytical studies were challenged by several investigators who pointed out methodical problems (Zayed et al 1992;Lukaszewski et al 1993;Hagemeyer et al 1994). A fundamental assumption is that absorbed trace elements are incorporated more or less exclusively in wood of the recently developing, outermost growth ring.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, a separate study revealed inverse correlations amid herbicide phytotoxicity and the activity of the plant's GSH conjugating system which signifies the tolerance of poplars against chloroacetanilide herbicide and highlights plant's capability to detoxify these herbicides via GSH conjugation (Kömives et al 2003a). Above-ground tissues of P. marilandica were determined with considerable superaccumulation efficiency for metals, and it has been recommended as a tree for land reclamation (Rachwal et al 1992;Lukaszewski et al 1993;Giniyatullin et al 1998). Owing to its extensive root system, hydroponic cultures of hybrid poplar tree were reported to be potential phytoremediator for organic pollutants (Aitchison et al 2000).…”
Section: Phytostabilization and Phytovolatilizationmentioning
confidence: 99%